Temperature profiles under the ceiling of subway train inside a tunnel with longitudinal ventilation - Zhenkun Wu; Min Peng; Xiaolei Zhang; Xuyao Qi; Wenxuan Miao; Ding Li; Dongzi Qin (Tunnelling and Underground Space Technology, 2026)

How pyruvate postpones postharvest physiological deterioration of cassava - Yannian Che; Chen Shen; Xiaohua Lu; Zhongping Ding; Yaxingqiao Zhou; Qin Zhou; Jiao Liu; Yajie Wang; Jianchun Guo; Yuan Yao; Alisdair R. Fernie; Ruimei Li (Postharvest Biology and Technology, 2026)

Current Advances in Microbial Degradation for Fluoroquinolones: Degraders, Mechanisms and Applications - Tongtong Liu; Qin Ding; Yuan Hong; Zhuoxiao Li; Rongli Sun; Juan Zhang (Reviews of Environmental Contamination and Toxicology, 2026)

Integrated computational and in vivo evidence prioritizes MYH6 as a candidate node in PFOS-associated HCM-like cardiac remodeling - Hao Gao; Li Ma; Shiyi Tan; Xulei Zuo; Wei Wang; Linlin Zhang; Qin Ding; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Mechanism of glyoxalase MeGLYI-13 in regulating postharvest physiological deterioration of cassava - Chen Shen; Yannian Che; Zhongping Ding; Qin Zhou; Yaxingqiao Zhou; Alisdair R. Fernie; Jiao Liu; Yajie Wang; Xiaohua Lu; Jianchun Guo; Yuan Yao; Ruimei Li (Postharvest Biology and Technology, 2026)

Impact of genetic modifications in starch biosynthesis on 3D printing performance of rice starches - Yaqi Hu; Ziliang Qin; Li Ding; Xiaoning Liu; Xingxun Liu; Deyong Zhu; Jacob Judas Kain Kirkensgaard; Tomasz Pawel Czaja; Sheng Chen; Andreas Blennow; Jiyu Yang; Jinsong Bao; et al. (Food Chemistry, 2026)

A combined metabolomic and sensory study on taste development in ‘Qiancha 1’ summer straight green tea processing - Ting Yang; Shimao Fang; Fengjiao Ding; Tuo Zhang; Yuqiao Dai; Zhongying Liu; Qin Li; Jinlong Luo; Qiang Shen; Ke Pan (Food Chemistry, 2026)

Technological innovation: Aspergillus niger single-strain-fermented Pu-erh tea significantly regulates lipid metabolism and obesity in C57BL/6J mice - Bai-Yu Xie; Lan Cai; Xiao-Qin Zhu; Ming-Gang Li; Jiang-Yuan Zhao; Zhang-Gui Ding (Food Bioscience, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Unravelling saltmarsh organic carbon sources: biomarker-isotopic integration for credible blue carbon accounting - Jinge Zhou; Hua He; Han Chen; Jingfan Zhang; Zhe Lu; Shuchai Gan; Guoming Qin; Lulu Zhang; Xingyun Huang; Neil Saintilan; Ding He; Yongxia Jia; et al. (CATENA, 2026)

Microbial carbon limitation shapes blue carbon quality during mangrove restoration - Xingyun Huang; Cantong Huang; Wensui Li; Fangyuan Guan; Guoming Qin; Zhe Lu; Jingwei Shi; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Hui Li; Shamim Ahmed; et al. (CATENA, 2026)

Impact of Microplastics on the Immobilization of Cd in Soil by Biochar - Ruoxuan Wang; Jiafu Ding; Xia Tian; Gui Ma; Meiyuan Li; Xiaohua Mai; Qin Ma; Cong Shen (Water, Air, & Soil Pollution, 2026)

Corrigendum to “Metabolomics combined with machine learning reveals candidate metabolites and a putative working network associated with cereulide production in emetic Bacillus cereus” [Food Res. Int. 239 (2026) 119523] - Ying Feng; Minling Chen; Jiaxun Li; Keyuan Qin; Moutong Chen; Juan Wang; Qingping Wu; Yuting Shang; Yu Ding (Food Research International, 2026)

Metabolomics combined with machine learning reveals candidate metabolites and a putative working network associated with cereulide production in emetic Bacillus cereus - Ying Feng; Minling Chen; Jiaxun Li; Keyuan Qin; Moutong Chen; Juan Wang; Qingping Wu; Yuting Shang; Yu Ding (Food Research International, 2026)

Effect of electrohydrodynamic drying on the drying characteristics and nutritional quality of lettuce - Xueru Zhu; Zhiqing Song; Bufan Li; Wenjie Cao; Liqiang Liu; Changjiang Ding; Chunxu Qin (Food Control, 2026)

Interrogating vascular determinants of repair: Biofabricated constructs for precision intervention in peripheral neuropathies - Mouyuan Sun; Shuangyang Li; Xuankai Fan; Yiqian Xu; Yaxian Luo; Luying Qin; Jingyu Zhang; Zhixu He; Lianjie Peng; Xinyi Feng; Tao Qiu; Tian Zhang; et al. (Chemical Engineering Journal, 2026)

Photothermal CO2 hydrogenation to methanol on MoO3@MoS2 core-shell structure catalyst - Langlang Qin; Yunfei Gao; Yage Wang; Qiannan Ding; Caiyun Han; Jinping Li; Shuang Wang (Chemical Engineering Journal, 2026)

Rewiring of Nestin+ Cells Through PTBP1/PKM2 Axis Restores Notch-Dependent Neural Circuit Regeneration After Spinal Cord Injury - Wei Hu; Meng Li; Yicheng Ding; Xinyi Cheng; Junchao Luo; Junjie Niu; Xiaozhong Zhou; Huilin Yang; Lulu Zhang; Qin Shi; Xingzhi Liu (Neuroscience Bulletin, 2026)

Nat10-mediated ac4C modification sustains macrophage proliferation and mitigates colitis progression via Mcm2 stabilization - Jinsong Wang; Tao Liu; Jiachen Zhao; Zhiqing Diao; Fuhong Fan; Demeng Qin; Yu Zhang; Xindi Wang; Ning Jiang; Chenbo Ding; Hua-Bing Li; Yuzhang Wu (Science China Life Sciences, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Three new ent -kaurene diterpenoid glucosides from the flowers of Inula japonica Thunb. - Zheng Niu; Jia-Qi Chen; Guan-Ke Liu; Li-Qin Ding; Chun-Yan Chen; Bing-Yang Zhang; Yu-Hong Li; De-Qin Zhang; Tie Yao; Feng Qiu (Natural Product Research, 2026)

Enhancing electret properties of stretchable FEP/Ecoflex triboelectric materials by quenching polarization - Long Zheng; Siyao Qin; Xucong Wang; Hao Gong; Xiaoliang Li; Yaoyi Guo; Zifei Meng; Shuai Ding; Ning Li; Xiangcheng Chu; Xiangyu Chen (Chemical Engineering Journal, 2026)

Non-linear responses of ecosystem service trade-offs to landscape heterogeneity: implications for spatially targeted landscape management in an urbanizing agricultural basin - Jiman Li; Henghui Xi; Fei Wang; Xue Ding; Xufei Chen; Yu Tao; Conghong Huang; Qin Tao; Xianbo Cheng; Weixin Ou (Landscape and Urban Planning, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Knowing when to stop: Threshold effects of human disturbance on ecosystem health in the Taihu Basin, China - Zhifan Ding; Hanyu Hu; Qinghua Xu; Xiaolan Hong; Mingcheng Li; Jiayu Qin; Ying Zhu; Hui Wang (Environmental Impact Assessment Review, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

A new amide alkaloid from the coculture liquid cultures of two grape endophytic fungi Penicillium sp. YPT103-2 and Penicillium sp. YPT104 - Yu-Qin Yang; Jin-Feng Cao; Juan-Juan Pu; Dong-Ping Li; Chuan-Mao Zhang; Zhi-Jian Wu; Jian-Hai Ding (Natural Product Research, 2026)

Hydrochemical characteristics and pollution sources of groundwater in the Zhuxihe River Basin, Hainan Province, China - Tongchun Qin; Yongpeng Yang; Ning Shan; Haiqin Ding; Lingling Cui; Zhiwei Li; Yuhui Zhang; Haigang Wang; Di Ning (Environmental Monitoring and Assessment, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Synthesis, characterization, and antimicrobial properties of 8-Hydroxyquinoline-based group 4 metal complexes for plant pathogen control - Tiankun Zhao; Baoqing Lv; Yinan Ding; Dongyu Mei; Jing Ma; Qi Zhang; Li Zhang; Qipin Qin; Zhongduo Yang; Shanjia Li; Isabel Correia; Hong Liang; et al. (Pesticide Biochemistry and Physiology, 2026)

Efficient persulfate activation via a novel layered porous biochar enhanced with nano-zero-valent iron loading and synergistic sulfidation modification: Performance and mechanism - Lei Shen; Zichen Qin; Yuanding Shi; Yan Li; Pengyao Guo; Jinwei Zhang; Yijun Shen; Chun Yang; Yuchen Zeng; Dongxiao Sun; Zhiqiang Dong; Lei Ding (Journal of Water Process Engineering, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

Imbalanced Si:N Alters Lipid Production and Photosynthesis in the Marine Diatom Phaeodactylum tricornutum and Dinoflagellate Prorocentrum donghaiense - Jiaxuan Cui; Chuanli Zhang; Rong Bi; Yunyun Zhuang; Xiaoqian Pan; Xiao Qin; Zhong Cao; Hailong Zhang; Li Li; Yang Ding; Meixun Zhao (Journal of Ocean University of China, 2026)

Cover Image - Yinnan Mu; Weini Zhang; Pan Qin; Wenxing Li; Zhengwei Cui; Yang Ding; Jingqun Ao; Jiangtao Gao; Xinhua Chen (Reviews in Aquaculture, 2026)
The cover image is based on the article Elucidating the Immunological Basis of Large Yellow Croaker Larimichthys crocea Offers New Strategies for Its Disease Management by Yinnan Mu et al., https://doi.org/10.1111/raq.70164 . image

Elucidating the Immunological Basis of Large Yellow Croaker Larimichthys crocea Offers New Strategies for Its Disease Management - Yinnan Mu; Weini Zhang; Pan Qin; Wenxing Li; Zhengwei Cui; Yang Ding; Jingqun Ao; Jiangtao Gao; Xinhua Chen (Reviews in Aquaculture, 2026)
Large yellow croaker Larimichthys crocea is a major mariculture species in China, achieving an annual yield of 292,615 tons by 2024. Commercial production faces considerable challenges from disease outbreaks, necessitating comprehensive immune mechanism research. Through comprehensive genomic and transcriptomic investigations, scientists have identified distinguishing characteristics within the L. crocea immune system, encompassing robust innate defense mechanisms, marked by the expansion of pattern recognition receptor lineages, antimicrobial peptide gene families, and antiviral defense‐related genes, and well‐developed adaptive immune capabilities. The current review outlines the molecular foundations underlying immune responses in L. crocea , highlighting the cooperative interplay between innate and adaptive defense systems when confronting pathogenic threats and environmental fluctuations. It bridges basic scientific inquiry with practical aquaculture implementation, exploring disease control strategies. Available evidence indicates possibilities for strengthening disease resistance through precision immunomodulation and improved aquaculture methods. Priority research areas encompass elucidating host‐pathogen relationships and establishing practical disease prevention protocols for industrial‐scale operations.

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Paeoniae Radix Alba polysaccharides: Structural characterization, macrophage immunomodulation, and potent vaccine adjuvant activity - Ming Zhao; Yushi Wang; Ran Guan; Shiyue Qin; Guoqiu Li; Jiaqi Wang; Zhiye Wang; Junyan Shang; Lingyi Xu; Qingrui Lin; Yanxia Ding; Xiaodan Ma; et al. (Carbohydrate Polymers, 2026)

Gut microbiota-tryptophan-serotonin axis drives anxiety-like behavior via NLRP3-mediated neuronal pyroptosis in the medial prefrontal cortex - Guiqiang Zhou; Xing Wang; Tongzhou Qin; Ling Guo; Jiajin Lin; Zhaowen Zhang; Peng Gao; Yan Zhou; Wei He; Jing Li; Guirong Ding (Apoptosis, 2026)

Treatment performance and mechanism of source-separated blackwater using an earthworm-based reactor for rural applications - Le Zhong; Guang-Feng Liu; Shi-Chao Liang; Jie Ding; Han-Jun Sun; Ding-Ding Tang; Yan Zhou; Xiong Qin; Ji-Wei Pang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2026)

The hydroxyl content of biochar mediates the coating structure to dominate the release performance of castor oil-based polyurethane coated urea - Zexi Li; Yufeng Chen; Ruhong Qin; Qianqian Dai; Chunxia Ding; A-juan Zhao; Xiangrong Liu; Fangfang Wu; Mei-e Zhong (Environmental Research, 2026)

H2 norm based active multiple tuned mass dampers optimization for resonance suppression with robust stability constraint - Jianqiang Yao; Haode Huo; Yunzhi Zhang; Qin Li; Wentao Li; Chenyang Ding (Engineering Structures, 2026)

High-pressure structural evolution of talc investigated by X-ray diffraction, infrared spectroscopy, and density functional theory calculations - Bingxu Hou; Jingjing Niu; Lili Zhang; Hongrui Ding; Fei Qin; Yanzhang Li; Shan Qin; Anhuai Lu; Hongyan Zuo (Applied Clay Science, 2026)

Effects of paternal 5G RFR exposure on health of male offspring mice - Zhang Zhaowen; Guo Ling; Zhou Guiqiang; Lin Jiajin; Qin Tongzhou; Li Jiangyi; Li Jing; Wang Fuli; Ding Guirong (Reproductive Toxicology, 2026)

Isolation and identification of Bacillus velezensis Bac302 and its biocontrol potential against Alternaria tenuissima causing leaf blight on Schisandra chinensis - Xiaojie Ding; Yequan Qin; Ziyang Liu; Zhiguo Liu; Bing Li; Zibo Li; Rujun Zhou (Physiological and Molecular Plant Pathology, 2026)

Improving ignition and combustion of B/KClO4 by introducing polyethylene glycol as a surfactant - Honghong Qin; Wenzhe Ma; Li Ding; Chong Wan; Qingguang Zhu; Suhang Chen; Fengqi Zhao; Kangzhen Xu (Fuel, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

Comparative analysis of microplastics in aquatic environments: Matching thresholds, abundance versus mass concentration, and risk assessment - Weiping Mei; Jibing Li; Xiaoyan Ding; Shihong Liu; Shibin Qin; Xiaochun Wang; Chunling Luo (Environmental Pollution, 2026)

Effects of vermicompost on maize growth, soil aggregate stability, and microbial community dynamics in saline-alkali soil - Xue Qin; Tiegen Bai; Kui Huang; Yali Huang; Zaixing Li; Changxiong Zhu; Jungang Ding; Menglu Li (Applied Soil Ecology, 2026)

COL8A1-positive cancer-associated fibroblasts are drivers of 5-fluorouracil resistance in colorectal cancer - Muzi Ding; Yue Li; Zixuan Liu; Shangshang Hu; Jinwei Lou; Yuhan Chen; Jian Qin; Mu Xu; Huiling Sun; Tao Xu; Shukui Wang; Yuqin Pan (Apoptosis, 2026)

Prediction Model for Maritime 5G Signal Strength Based on ConvLSTM-PSO-XGBoost Algorithm - Jianjun Ding; Kun Yang; Li Qin; Bing Zheng (Journal of Marine Science and Engineering, 2026)
The accurate prediction of signal strength plays an important role in estimating radio signal quality, thus forming the essential foundation for the planning, optimization, and reliable operation of modern wireless network systems. This paper proposes a new hybrid model for predicting maritime 5G signal strength, combing Convolutional Long Short-Term Memory (ConvLSTM) with Particle Swarm Optimization-extreme Gradient Boosting (PSO-XGBoost). The model was developed and validated using a dataset comprising 22 columns, 2994 rows, and 21 features, collected via a research vessel in Zhoushan Port, China. Four evaluation metrics, Root Mean Square Error (RMSE), Mean Absolute Error (MAE), Mean Absolute Percentage Error (MAPE), and the coefficient of determination (R2) were employed to assess model performance and interpretability. Comparative experiments against various popular models demonstrated the hybrid model’s superior performance in predicting maritime 5G signals. Its accuracy surpassed both standalone ConvLSTM and XGBoost models, while achieving lower MAE and RMSE values compared to various popular models. This study provides a method for predicting coverage conditions based on navigation and environmental data, without relying on radio key performance indicators. Furthermore, it supplies high-quality signal data to advance the modeling of marine communication channels.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Global, regional, and national burden of hepatocellular carcinoma and contribution of nine modifiable risk factors across 185 countries/territories in 2022 - Ping Li; Zhan Ding; Yuqi Feng; Xiangyu Ren; Yongyue Wei; Changfa Xia; Yitao Yang; Quanbo Yang; Zhe Wang; Xuehong Zhang; L.G. van der Geest; Herbert Yu; et al. (Science Bulletin, 2026)

Humidity-responsive composite film for strawberry freshness control - Sulin You; Hui Li; Zilin Qi; Hengping Xu; Tianhua Ding; Zainab Rasheed; Mingrui Chen; Wen Qin; Suqing Li; Yaowen Liu (Journal of Food Engineering, 2026)

Material source and genesis analysis of lithium-rich claystone in Balun Mahai Salt Lake, Qaidam Basin - Fan Zhang; Xiwei Qin; Yuliang Ma; Sha Yang; Tong Pan; Jianzhou Chen; Chenglin Liu; Chengwang Ding; Ziwen Jiang; Dong Zhang; Qingkuan Li; Genhou Wang; et al. (Journal of Geochemical Exploration, 2026)

Upwelling enhances cycling and emissions of very short-lived halocarbons: Biogeochemical mechanisms and climate feedbacks - Ya-Wen Zou; Qin-Sheng Wei; Cheng-Xuan Li; Xing Zhai; Ming Xin; Xiao-Meng Duan; Hui Ding; Baodong Wang (Global and Planetary Change, 2026)

Research progress on spike development of wheat - Yi Ding; Ying Zhang; Tengteng Zhang; Dan Zhao; Yufeng Yang; Kaiyue Wang; Ziqi Zheng; Chaoran Wang; Yongpeng Li; Runya Mao; Yifan Ye; Mengxue Li; et al. (Plant Science, 2026)

PtPd/CeO2 catalytic enhanced WO3 nanofibers bilayer gas sensor for ppb-level xylene detection - Manwen Hu; Jiejie Yu; Ruijie Qin; Jinwu Hu; Jingcheng Xu; Hui-jun Li; Hui Xu; Jingbo Chen; Ding Wang (Journal of Hazardous Materials, 2026)

Photothermal CO2 hydrogenation to methanol on MoS2 with morphology and sulfur vacancies tuning - Langlang Qin; Yunfei Gao; Caiyun Han; Qiannan Ding; Shuang Wang; Jinping Li (Fuel, 2026)

Metabolomic insights into the role of isoleucine in regulating cereulide biosynthesis in emetic Bacillus cereus - Jiaxun Li; Keyuan Qin; Yuting Shang; Zhenjun Zhu; Yangfu Li; Junhui Wu; Moutong Chen; Liang Xue; Qingping Wu; Juan Wang; Yu Ding (Food Research International, 2026)

Intelligent food preservation systems based on MOFs-AI integration: technological breakthroughs and developmental trends - Xin Ding; Nasi Ai; Yiming Zhao; Lingyun Li; Ge Chen; Donghui Xu; Xiaomin Xu; Lin Qin; Jing Chen; Guangyang Liu (Food Chemistry, 2026)

Degradation of roxarsone via peroxymonosulfate activation by CoFe₂O₄-loaded biochar: Efficiency and mechanisms - Pengyao Guo; Yuan Qin; Lei Ding; Yujie Fang; Yan Li; Yiming Zong (Chemical Engineering Journal, 2026)

Isotopic inference of atmospheric nitrate sources and formation pathways: Significant biases introduced by non-negligible primary nitrate emissions - Hao Xiao; Qin-Kai Li; Shi-Yuan Ding; Xiao-Dong Li (Atmospheric Research, 2026)

Inversion of hourly NOx emissions through air quality monitoring data and deep learning response surface modeling - Ziyi Liu; Yun Zhu; Ji-cheng Jang; Zhaoxin Dong; Jia Xing; Bin Zhao; Jinying Li; Qipeng Wen; Dian Ding; Yujie Qin (Atmospheric Environment, 2026)

Lactiplantibacillus plantarum Ameliorated Growth Performance and Intestinal Inflammation by Modulating Gut Microbial Structure and Function of Yellow River Carp (Cyprinus carpio) - Lijiao Cheng; Junxiang Ding; Wenli Liu; Yijie Li; Chaobin Qin; Liping Yang; Xiao Yan; Guoxing Nie (Probiotics and Antimicrobial Proteins, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

High-level expression of zearalenone lactonohydrolase ZenG in Pichia pastoris via combinatorial strategy - Qin Zhou; Shida Zhao; Yuzhuo Wu; Yanfei Sun; Qi Wu; Qi Li; Ding Li; Jianhong Xu (Archives of Microbiology, 2026)

Biodegradable film combined with ploughing: An approach to improve the sustainability of rainfed spring maize production - Rui Qian; Luning Du; Wenjing Li; Wei Wang; Yang Zhang; Yujie Gao; Wenjing Feng; Jiaji Ding; Wenbo Lv; Pengyao Qin; Tie Cai; Xiaolong Ren; et al. (Soil and Tillage Research, 2025)

Soil moisture variability of typical mixed forests in the north-south climatic transitional zone of China - Yu Mei; Qinghe Zhao; Peikun Li; Xiaojian Qin; Boxuan Liu; Zhize Li; Tingting Wang; Shengyan Ding (Journal of Environmental Management, 2025)

Unveiling the mastery of bacterial navigation: The role of methyl-accepting chemotactic proteins in sensing and mobility through environments and their promising applications in food sustainability - Jiaxun Li; Salma A. Bekhit; Guicheng Zhou; Yangfu Li; Xinmin Liang; Keyuan Qin; Moutong Chen; Liang Xue; Alaa E.-D.A. Bekhit; Juan Wang; Qingping Wu; Yu Ding (Food Research International, 2025)

Impact of esterification degree of pectic polysaccharides from quinoa microgreen on protective effects against dextran sulfate sodium-induced colitis in mice - Wang Guo; Bo Li; Mao-Qing Wang; Yang Cao; Qin Yuan; Wen Liu; Yi-Chen Hu; Liang Zou; Shengpeng Wang; Ding-Tao Wu (Food Bioscience, 2025)

Environmental chromium and cadmium co-exposure induces GADD45A-mediated rDNA instability in human cohorts and cell models - Yongxin Li; Yao Qin; Chuyan Zhang; Chan Ding; Minqian Feng; Yifan Dou; Xinran Wang; Xia Rao; Xiaoxue Gong; Zhaoqiang Jiang; Jianlin Lou; Huadong Xu (Chemico-Biological Interactions, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

ERO1A-positive tumor epithelial cells in colorectal cancer progression: a multi-omics perspective - Shangshang Hu; Jinwei Lou; Yuhan Chen; Muzi Ding; Jian Qin; Junjie Nie; Yue Li; Zixuan Liu; Mu Xu; Huiling Sun; Qianni Xiao; Yuqin Pan; et al. (Apoptosis, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

A protein structure-dependent fluorescent probe for real-time β-lactoglobulin detection - Xian-Ting Yan; Wen-Xuan Qin; Kai-Li Chang; Hong-Kai Bian; Xin-Yu Pan; Xiang Ding; Wen-Bo Liu; Qing Wang (Food Chemistry, 2025)

Investigation of the matrix effects on structural stability and application performance of aptamers: Insights from tetrodotoxin detection in typical seafood - Yu Li; Shuo Qi; Peifang Chen; Mingwei Qin; Ning Ding; Chifang Peng; Zhouping Wang (Food Chemistry, 2025)

Bi-directional pH-responsive cellulose nanocrystals-based pesticide microcapsules for sustainable agriculture - Jia-wei Ding; Li-na Guo; Shu-heng Li; Qin Gao; Wang Wu; De-qiang Li; Jun Li (Carbohydrate Polymers, 2025)

Recent advances in Pyrazolo[3,4-d]pyrimidine-based dual inhibitors in the treatment of cancers - Hanrui Jiang; Nan Li; Ruosong Qin; Siyu Lin; Xuelian Wang; Chunyan Li; Jiwei Shen; Ye Chen; Ju Liu; Shi Ding (Molecular Diversity, 2025)

Devonian–Triassic tectonic evolution of the Western Qinling Orogenic Belt of central China: Insights from detrital zircon U Pb chronology and rock geochemistry - Yan Zhang; Shuang Dai; Futian Liu; Dongbao Guo; Lingfeng Qin; Zhongzhao Ding; Yongfa Chen; Xinnan Fang; Xiaojun Ma; Yu Wang; Hua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

S-scheme TiO2/biochar heterojunction derived from waste rice noodles: a low-cost waste-to-catalyst strategy for enhanced photocatalytic hydrogen production - Guangzhi Qin; Chuanyang Tang; Yang Yang; Guanzhi Ding; Minghui Li; Shuoping Chen (Chemical Engineering Journal, 2025)

Photothermal-driven micromotor for enhanced lithium extraction from salt-lake brines - Shihao Ding; Wenqian Xing; Ling Chen; Linhui Fu; Xinle Zhang; Zhen Luo; Qianqian Li; Mengting Qin; Jiang Gong; Jinping Qu; Ran Niu (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from the stems of Daphniphyllum angustifolium Hutch. and their chemotaxonomic significance - Xiao-Juan Huang; Heng-Gang Zhang; Xiao-Hong Li; Yu-Bin Wei; Khalid-Hassan Mohamed; Chang-Qin Yin; Hao-Fei Yu; Cai-Feng Ding; Lan-Chun Zhang (Biochemical Systematics and Ecology, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

How do water quality requirements and spatial flows shape the supply-demand balance of water provision ecosystem services? Evidence from the Taihu Lake Basin - Xue Ding; Yu Tao; Jinling Luo; Henghui Xi; Qin Tao; Jiman Li; Conghong Huang; Fengyi Du; Weixin Ou (Applied Geography, 2025)

Heterologous expression of Pyrenocine A from Colletotrichum gloeosporioides CGMCC 3.17371 - Chao Chen; Yuxin Shi; Haizhifei Ding; Lina Yu; Wei Lin; Jianbin Xiao; Huaidong Zhang; Qin Li; Mingliang Zhang; Li Li (Natural Product Research, 2025)

Genomic characterization of Gillisia xinjiangensis sp. nov.: insights into nitrogen metabolism, stress adaptation, and application potential - Hao-hao Wang; Chi Zhang; Ya-qin Chen; Yi-fan Guo; Li-jian Ding; Sheng-fa Zhang; Gai-jun Du; Wei-yan Zhang; Shan He (Systematic and Applied Microbiology, 2025)

Lipid droplet clearance inhibits esophageal cancer growth via metabolic reprogramming - Yan Pu; Yi Wan; Yuhua Fu; Kai Li; Yijiao Chen; Yunzhi Wang; Bin Li; Lingling Li; Zhaoyu Qin; Jingyan Xu; Dongxian Jiang; Yan Li; et al. (Science Bulletin, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Pectic polysaccharides from unripe and mature kiwifruit alleviate ulcerative colitis by modulating gut microbiota and restoring the intestinal barrier - Kai-Xin Jiang; Jin-Lei Geng; Qin Yuan; Jie Li; Wen Liu; Hong-Yan Liu; Yi-Chen Hu; Liang Zou; Shengpeng Wang; Ding-Tao Wu (Food Bioscience, 2025)

Corrigendum to “TDCPP disrupts ALG-2/ALIX-mediated ESCRT-III recruitment: Implications for lysosomal membrane repair and neurotoxicity” [Environ. Pollut. 379 (2025) 126535] - Tingting Li; Yue Zhang; Xueman Ding; Li Liu; Runjiang Ma; Wenqi Qin; Chulin Yan; Chun Wang; Jingjing Zhang; Mulatibieke Keerman; Qiang Niu (Environmental Pollution, 2025)

Initiative invasion promoted photoelectrocatalytic antibacterial function on ZIF-67@CoO@Co foil photoanode - Mengna Ding; Qin Zhang; Fengyan Shi; Liping Zhou; Xinchun Guo; Qiuyue Li; Liulin Luo; Yingchun Miao; Yuning Huo (Chemical Engineering Journal, 2025)

High-barrier bacterial cellulose/polyvinyl alcohol based active packaging material for food preservation - You Li; Wenjia Han; Qijun Ding; Deyuan Yang; Xungan Li; Zhuqing Liu; Qin Wu (Carbohydrate Polymers, 2025)

Mesh-Free Method for Static Analyses of Carbon Nanotube-Reinforced Composite Plates - Peng-chu Ding; Qin-qiang Guo; Li-wu Chang; Jun-feng Xu; Zhen Li; Shi-heng Yan; Dong Han (Applied Geophysics, 2025)

Antifungal activity and underlying mechanism of action of paeonol against Sclerotium rolfsii - Chunlan Shi; Hongmei Li; Dewei Yang; Lirong Chen; Kaichen Guan; Xiaoping Qin; Deqiang Qin; Xi Gao; Xiao Ding; Guoxing Wu (Pesticide Biochemistry and Physiology, 2025)

Corrigendum to “F-53B disrupts energy metabolism by inhibiting the V-ATPase-AMPK axis in neuronal cells,” [ J. Hazard Mater. (487 (2025) 137111] - Yue Zhang; Tingting Li; Xueman Ding; Li Liu; Runjiang Ma; Wenqi Qin; Chulin Yan; Chun Wang; Jingjing Zhang; Mulatibieke Keerman; Qiang Niu (Journal of Hazardous Materials, 2025)

Facile fabrication of ethyl cellulose/gelatin fibers incorporated with copper-based metal-organic frameworks as humidity-triggered release of carvacrol for blueberry preservation - Jing Xie; Xingyu Rong; Xiaoqian Jiang; Yuping Zhao; Tianhua Ding; Jing Yan; Suqing Li; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

TDCPP disrupts ALG-2/ALIX-mediated ESCRT-III recruitment: Implications for lysosomal membrane repair and neurotoxicity - Tingting Li; Yue Zhang; Xueman Ding; Li Liu; Runjiang Ma; Wenqi Qin; Chulin Yan; Chun Wang; Jingjing Zhang; Mulatibieke Keerman; Qiang Niu (Environmental Pollution, 2025)

Immunomodulatory Effects of Lactiplantibacillus plantarum Strain RW1 During Salmonella Infection in Murine Intestinal Epithelial Cells and Dextran Sulfate Sodium-Induced Murine Colitis - Guangzhi Zhang; Abdul Raheem; Xiaofeng Xu; Xuezheng Fan; Jianwei Zhang; Tong Qin; Li Jia; Min Yue; Weifang Yang; Liang Wang; Mingyan Wang; Yajie Yin; et al. (Probiotics and Antimicrobial Proteins, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Late Oligocene paleosols in the Haltang Basin of northeastern Tibetan Plateau and their implications for the early extent of the Asian monsoon - Zhaobin Zhang; Shuang Dai; Xinnan Fang; Xiaojun Ma; Yufan Zhang; Zhongzhao Ding; Lingfeng Qin; Chunyan Li; Meng Zhou; Tianqi Ji; Jie Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Combined Effects of Cadmium and Microplastics on the Wheat (Triticum aestivum L.) Plant-Soil System with the Partial Least Square Model: Phytotoxicity and Soil Properties - Yue Chen; Ding Qin; Fupeng Chen; Haitao Liu; Di Lin; Lantao Li (Journal of Soil Science and Plant Nutrition, 2025)

Per- and polyfluoroalkyl substances (PFAS) in drinking water systems in the lower Yangtze River: source, fate, and health risk assessment - Yuan Hong; Qin Ding; Tingting Yang; Xiaoqin Li; Ninghui Song; Juan Zhang (Environmental Geochemistry and Health, 2025)

New insights of subsistence practices in the late Shang period of upper reaches of Hutuo river, Xinding basin, Shanxi Province: lipid residue evidence - Li Ding; Lizhi Wang; Qiang Lyu; Qin Yang; Yimin Yang (Archaeological and Anthropological Sciences, 2025)

An Integrated Safety Monitoring and Pre-Warning System for Fishing Vessels - Kun Yang; Jinglong Lin; Jianjun Ding; Bing Zheng; Li Qin (Journal of Marine Science and Engineering, 2025)
Fishing vessels are essential for the activities of catching, moving, and storing fish. However, fishing vessel accidents claim thousands of deaths every year. This study presents a novel integrated safety monitoring and early warning system designed for fishing vessels, offering significant advancements in maritime safety through real-time alerts based on vessel attitude motion and environmental conditions. The innovation of the system lies in its dual-subsystem architecture: a sensing terminal equipped with a nine-axis sensor, temperature and humidity sensors, a GPS module, and a surveillance camera collects critical data, while a decision support subsystem processes this information via a fuzzy logic-based algorithm to generate a “danger score”. This score quantifies the vessel’s safety status, enabling the system to trigger alerts through SMS and web notifications when predefined thresholds are exceeded. Field trials in the Zhoushan Sea area confirmed the system’s effectiveness in accurately predicting safety hazards and providing timely alerts. The results highlight its potential to enhance operational safety and contribute to the digitization of fisheries management by offering reliable real-time data on vessel conditions. The system’s modular and cost-efficient design ensures it is scalable and adaptable for widespread use across the fishing industry. Our study addresses the limitations of existing technologies by providing a balanced solution that combines comprehensive sensing capabilities with real-time responsiveness and cost-effectiveness, offering a practical and innovative approach to improve fishing vessel safety.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Study on phase transformation and dealkalization of red mud in NaOH-Ca(OH)2 system and CO2 adsorption performance of dealkalization residue - Wenbao Liu; Rui Ding; Weichao Li; Changye Mang; Sikai Zhao; Wengang Liu; Yanbai Shen; Qin Zhang (Process Safety and Environmental Protection, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

Purification efficacy and mechanism of two constructed wetlands on low C/N agricultural surface runoff pollutants and fluoroquinolone antibiotics - Yali Tan; Jiajun Wang; Qin Zhang; Dandan Xu; Jieyue Li; Yanli Ding; Shaoyuan Bai (Journal of Water Process Engineering, 2025)

F-53B disrupts energy metabolism by inhibiting the V-ATPase-AMPK axis in neuronal cells - Yue Zhang; Tingting Li; Xueman Ding; Li Liu; Runjiang Ma; Wenqi Qin; Chulin Yan; Chun Wang; Jingjing Zhang; Mulatibieke Keerman; Qiang Niu (Journal of Hazardous Materials, 2025)

A key amino acid substitution of vacuolar-type H+-ATPases A subunit (VATP-A) confers selective toxicity of a potential botanical insecticide, periplocoside P (PSP), in Mythimna separata and Spodoptera exigua - Xianxia Zhang; Yayun Zuo; Rui Liu; Shuang Wen; Yakun Pei; Qin Zhao; Baojun Shi; Wenjun Wu; Ding Li; Zhaonong Hu (Insect Biochemistry and Molecular Biology, 2025)

IGF2BP3 suppresses ferroptosis in lung adenocarcinoma by m6A-dependent regulation of TFAP2A to transcriptionally activate SLC7A11/GPX4 - Pengpeng Li; Dan Chu; Guangcheng Ding; Dehua Qin; Yajing Bu; Bi Tian (Molecular and Cellular Biochemistry, 2025)

Carbon dioxide–induced acidification enhances short‐lived brominated hydrocarbons production in oligotrophic oceans - Ya‐Wen Zou; Cheng‐Xuan Li; Qin‐Sheng Wei; Qian‐Yao Ma; Hui Ding; Xiao Meng Duan; Xing Zhai; Bao‐Dong Wang (Limnology and Oceanography, 2025)
Oceanic emission is a primary source of brominated very short‐lived substances (BrVSLs) to the atmosphere, which have important effects on stratospheric ozone chemistry. Marine biogeochemical processes regulating BrVSLs are often sensitive to ocean acidification. Yet, the response of BrVSLs production to acidification remains poorly understood. Herein, the effects of acidification on the production of two main BrVSLs, dibromomethane (CH 2 Br 2 ) and tribromomethane (CHBr 3 ), were studied by ship‐based incubation experiments at three stations in the South Atlantic and Indian Oceans. The average CH 2 Br 2 and CHBr 3 concentrations increased by 17.2–58.7% and 14.3–80.3% due to acidification under the in situ nutrient conditions with nutrient and/or iron limitation at the three stations, but the mechanisms driving these increases varied among different regions. The increased bromoperoxidase (BrPO) activity caused by acidification facilitated BrVSLs release in the Eastern Tropical Indian Ocean, where diatoms were dominant. CHBr 3 increased due to acidification as a result of enhanced reactivity of dissolved organic matter (DOM) in the Eastern Tropical Atlantic, where dinoflagellates were dominant. Brominated very short‐lived substances increased due to acidification as a result of a combined effect of the above two mechanisms in the Benguela Current Coastal with high phytoplankton abundance. Under the nutrient and/or iron addition conditions with nutrient and iron sufficiency, however, acidification did not promote BrVSLs production due to its only minor effect on the BrPO activity and reactivity of DOM, partly because the effect of increased oxidative stress was offset by that of changed phytoplankton composition. Our study provided a basis for future modeling on the impact of acidification on global BrVSLs emissions.

Effects of salt ions and pH on deamidated soybean protein hydrogels formation: Molecular structure, thermal aggregation and network - Tang-Hao Li; Yao-Qin Yang; Gao-Shang Wang; Ding-Yang Lv; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Chemistry, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

The regulation of ovarian degeneration in Pampus argenteus by heat shock protein genes under low‐temperature stress - Chunlai Qin; Chang Li; Ming Ding; Yi Wang; Yaya Li; Yajun Wang; Xubo Wang; Chunyang Guo (Journal of Fish Biology, 2025)
Temperature is a crucial environmental factor that significantly impacts the growth, development, metabolism, and physiological functions of fish. To study the effects of low‐temperature on the gonadal development of silver pomfret ( Pampus argenteus ), a cold period by gradually lowering the water temperature from 18°C to 9°C was simulated. The results showed that hsp70 , hsp90a , and hsp90b were widely expressed in the tissues of P. argenteus , with hsp70 primarily expressed in the pituitary, hsp90a and hsp90b mainly expressed in the lateral. The hsps were involved in the development process of P. argenteus from 1 to 27 days post‐hatching (dph). The expression levels of hsp70 and hsp90b were highest at 17 dph, while the levels of hsp90a were at 25 dph. Under the condition of 9°C, regressed oocyte were observed in the ovaries, the oocyte diameter significantly decreased, and the ovaries degenerated 100% after low‐temperature stress. The expression levels of hsps in the ovaries were significantly higher than in the control group, while the expression levels in the testes were significantly lower than in the control group. Taken together, hsps may regulate the ovarian degeneration under low‐temperature stress. Male fish rapidly completed meiosis and maintained the testes in the prophase of meiosis to resist the low‐temperature stress.

Altered resting-state functional connectivity of amygdala subregions in adults with subthreshold depression after aerobic exercise - Yihe Wang; Mengqi Zhao; Qin Li; Zeqi Hao; Jiaxi Zhang; Lina Huang; Qingguo Ding; Zhixiang Cheng; Jianxin Zhang; Huayun Li; Xize Jia (Brain Imaging and Behavior, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Temporal and spatial changes of glacial lakes in the central Himalayas and their response to climate change based on multi-source remote sensing data - Xiaoqiang Cheng; Donghui Shangguan; Chengsheng Yang; Wangping Li; Zhaoye Zhou; Xiaojie Liu; Da Li; Xiuxia Zhang; Huilan Ding; Zewei Liu; Yi Yu; Xiaoxian Wang; et al. (Global and Planetary Change, 2025)

Electronic engineering induced ultrafine non-noble nanoparticles for high-performance hydrogen evolution from ammonia borane hydrolysis - Siyuan Tang; Linlin Xu; Xiang Ding; Quanjiang Lv; Haotian Qin; Aosong Li; Xinchun Yang; Jian Han; Fuzhan Song (Fuel, 2025)

First successful inducing gynogenesis in Crassostrea angulata by inactivated tetraploid Crassostrea gigas sperm - Weitao Wan; Yanping Qin; Jinhui Wu; Haitao Ma; Chao Yue; Shengyong Li; Jiangwei Li; Zhongyu Wang; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; et al. (Aquaculture, 2025)

Elastomer foam templated three dimensional hybrid hydrogels for heterogeneously integrated stretchable electronics - Changqing Qin; Qian Wang; Ting Fang; Lin Wang; Cheng Yang; Yong Lin; Chong Bai; Wenqiang He; Likang Ding; Jinheng Zhang; Dongchan Li; Desheng Kong (Chemical Engineering Journal, 2025)

The role of the morphological motifs in syngas product selectivity during CO2 photoreduction - Hao Song; Hangmin Xu; Chuanzhou Bi; Ganghua Zhou; Xiang Liu; Kang Zhong; Jinman Yang; Qin Lei; Lvzhou Li; Huan Pang; Xingwang Zhu; Jianning Ding (Chemical Engineering Journal, 2025)

Hydrogen-Bonded organic framework Containing stacked Cu2+ for photocatalytic reduction of CO2 to C2H4 - Mengmeng Zhou; Debo Ding; Yansong Shi; Keke Wang; Qin Wang; Xiahe Chen; Hai-Min Shen; Teng-Shuo Zhang; Yun-Fang Yang; Jiexiang Xia; Huaming Li; Yuanbin She (Chemical Engineering Journal, 2025)

Associations of Urinary Nickel with NAFLD and Liver Fibrosis in the USA: A Nationwide Cross‑Sectional Study - Kening Zhang; Chunxiao Yang; Xue Zhao; Yuanyuan Wang; Zhuo Gu; Ruiming Yang; Haiyan Ding; Shuangshuang Li; Jian Qin; Xia Chu (Biological Trace Element Research, 2025)

Self-enriching anammox bacteria and in situ establishing anammox process in traditional wastewater treatment system - Xiang Ding; Yalin Li; Jixiang Zhao; Yuanyuan Miao; Danchen Zhao; Yitong Li; Zhongxiu Gao; Junhui Shi; Qin Wang; Xuejun Bi; Jianhua Zhang (Journal of Water Process Engineering, 2024)

Responses of depth-dependence of C:N:P stoichiometry to check dam in mangrove wetlands - Xingyun Huang; Fangyuan Guan; Yi Zhong; Yu Ni; Ruyi Ding; Guoming Qin; Jinge Zhou; Jingfan Zhang; Han Chen; Hua He; Yingwen Li; Yongxing Li; et al. (Journal of Environmental Management, 2024)

Remote sensing of air pollutants in China to study the effects of emission reduction policies on air quality - Gerrit de Leeuw; Ronald van der A; Jianhui Bai; Mirjam den Hoed; Jieying Ding; Jianping Guo; Zhengqiang Li; Ying Zhang; Cheng Fan; Kai Qin; Selviga Sinnathamby; Sarah Safieddine; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Comparative study of the rheology and texture of konjac glucomannan-xanthan gum complexes in water and simulated gastric fluid and their effect on gastric emptying - Wenjing Chen; Ding An; Mahmoud Youssef; Jiabin Qin; Hongshan Liang; Jing Li; Bin Li (Food Hydrocolloids, 2024)

Incorporating embodied carbon transfer and sequestration service flows into regional carbon neutrality assessment in China - Henghui Xi; Xiaodan Liu; Xue Ding; Conghong Huang; Yu Tao; Qin Tao; Jiman Li; Xianbo Cheng; Fei Wang; Weixin Ou (Sustainable Production and Consumption, 2024)

Microplastic exposure inhibits nitrate uptake and assimilation in wheat plants - Xian Zhi Fang; Shu Qin Fang; Yue Ding; Jia Wei Ma; Zheng Qian Ye; Dan Liu; Ke Li Zhao (Environmental Pollution, 2024)

Piperazine pyrophosphate-functionalized Ni-MOF metal framework: Fabrication and synergistic explosion suppression mechanisms - Yadi Li; Xiangbao Meng; Shizemin Song; Jihe Chen; Jianxu Ding; Xiaozhen Yu; Yujian Zhu; Zhao Qin (Chemical Engineering Journal, 2024)

Fate of soil organic carbon in estuarine mangroves: Evidences from stable isotopes and lignin biomarkers - Guoming Qin; Zhe Lu; Shuchai Gan; Lulu Zhang; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Xingyun Huang; Han Chen; Hua He; Mengxiao Yu; Hui Li; et al. (CATENA, 2024)

Corrigendum to “Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding” [Aquaculture 563 (2023) 738910] - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Reconstructing high-resolution gridded precipitation data in the southwest China highland canyon area using an improved (MGWR) downscaling method - Lihong Wang; Yuechen Li; Yushi Gan; Long Zhao; Lei Fan; Wei Qin; Lin Ding (Science of The Total Environment, 2024)

High sensitivity of dissolved organic carbon transport during hydrological events in a small subtropical karst catchment - Caiqing Qin; Si-Liang Li; Yiping Wu; Adrian M. Bass; Weijun Luo; Hu Ding; Fu-Jun Yue; Pan Zhang (Science of The Total Environment, 2024)

Sesquiterpene lactones from Tithonia diversifolia with ferroptosis-inducing activities - Ao-Xue Ding; Yi-Ming Shan; Chen-Yue Li; Guo-Qing Qin; Tong Chen; Qing Wang; Xiang-Gang Hu; Peng-Ju Guo; Hai-Jun Yu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

Formation of a transparent soy protein hydrogel: Controlled thermal aggregation of protein using glutaminase - Tang-Hao Li; Yao-Qin Yang; Ding-Yang Lv; Gao-Shang Wang; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2024)

Macroscopic behavior and kinetic mechanism of ammonium dihydrogen phosphate for suppressing polyethylene dust deflagration - Xiaozhen Yu; Xiangbao Meng; Jihe Chen; Yujian Zhu; Yadi Li; Zhao Qin; Jianxu Ding; Shizemin Song (Chemical Engineering Journal, 2024)

Size-dependent activity modulation of supported Ni nanocatalysts for efficient solid-state hydrogen storage in magnesium - Yifan Zhu; Zhikang Qin; Xiaobin Shi; Xiaoli Ding; Van-Duong Dao; Yongtao Li (Chemical Engineering Journal, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

EMS-induced missense mutation in TaCHLI-7D affects leaf color and yield-related traits in wheat - Zixu Wang; Huiyuan Xu; Faxiang Wang; Lingling Sun; Xiangrui Meng; Zhuochun Li; Chang Xie; Huijiao Jiang; Guangshuo Ding; Xinrong Hu; Yuhang Gao; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Strategies and mechanisms for improving the detection accuracy of nonextractable residues of polycyclic aromatic hydrocarbons in soils - Shibin Qin; Xiaoshui Li; Erxuan Han; Yuhan Fan; Shihong Liu; Yang Ding; Shihua Qi (Science of The Total Environment, 2024)

Molecular insights into the catalytic mechanism of a phthalate ester hydrolase - Ning Wang; Nan Zhang; Mei-Ling Sun; Yan Sun; Qing-Yu Dong; Yu Wang; Zeng-Tian Gu; Hai-Tao Ding; Qi-Long Qin; Yong Jiang; Xiu-Lan Chen; Yu-Zhong Zhang; et al. (Journal of Hazardous Materials, 2024)

Amorphous molybdenum sulfide nanosheets composed of [Mo3S13]2- active-site motifs for enhancing conversion of Fe3+/Fe2+ in Fenton reaction under neutral condition - Yue Li; Minghao Fan; Bo Yu; Conghui Wang; Xiang Yu; Jun Ding; Gang Qin; Lei Yan; Kai Yin; Longlu Wang (Chemical Engineering Journal, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

Fiddler crab bioturbation stimulates methane emissions in mangroves: Insights into microbial mechanisms - Guoming Qin; Zhe Lu; Shuchai Gan; Lulu Zhang; Jingtao Wu; Christian J. Sanders; Zhili He; Xiaoli Yu; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Xingyun Huang; et al. (Soil Biology and Biochemistry, 2024)

Assembly of core-shell Fe3O4 @CD-MOFs derived hollow magnetic microcubes for efficient extraction of hazardous substances: Plausible mechanisms for selective adsorption - Xingwei Xiang; Xiaoyan Mao; Xinqi Ding; Xiu Gu; Haorui Li; Ruizhi Liu; Yong Liu; Jiabin Jin; Lei Qin (Journal of Hazardous Materials, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Asymmetric non-fused ring acceptor with low energy loss for efficient organic solar cells - Yu-Chen Zhang; Meijia Chang; Jinwei Chen; Yamin Zhang; Yun-Tao Ding; Yongrui Yang; Yi-Guo Qin; Hao-Li Zhang (Chemical Engineering Journal, 2024)

A study on an accurate modeling for distinguishing nitrogen, phosphorous and potassium status in summer maize using in situ canopy hyperspectral data - Di Lin; Yue Chen; Yongliang Qiao; Ding Qin; Yuhong Miao; Kai Sheng; Lantao Li; Yilun Wang (Computers and Electronics in Agriculture, 2024)

Retarding anion migration for alleviating concentration polarization towards stable polymer lithium-metal batteries - Manying Cui; Yanyang Qin; Zhichao Li; Hongyang Zhao; Limin Liu; Zhiyuan Jiang; Zhenjiang Cao; Jianyun Zhao; Boyang Mao; Wei Yu; Yaqiong Su; R. Vasant Kumar; et al. (Science Bulletin, 2024)

Ergosterols with rare peroxide, oxetane ring moiety, and a lactone ring from Aspergillus spectabilis and their immunosuppressive activities - Mengsha Wei; Hong Liao; Qin Li; Xueying Deng; Chi Gao; Nanjin Ding; Weiguang Sun; Hucheng Zhu; Jieru Guo; Chunmei Chen; Yonghui Zhang (Phytochemistry, 2024)

Suitability of reduced dose glucocorticoids therapy regimen for antibody-associated vasculitis patients with TB: a retrospective study - Rui Wen; Jingni Xiao; Ning Ding; Yong Zhong; Qiong Yuan; Jiali Li; Qi Wang; Hebin Xie; Jiao Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Root-mediated acidification, phosphatase activity and the phosphorus-cycling microbial community enhance phosphorus mobilization in the rhizosphere of wetland plants - Cai Li; Xin Ma; Yan Wang; Qin Sun; Musong Chen; Chaosheng Zhang; Shiming Ding; Zhihui Dai (Water Research, 2024)

Long-term use of etomidate disrupts the intestinal homeostasis and nervous system in mice - Siming Ding; Kan Li; Xing Han; Wenting Lin; Yingjun Qin; Renjuan Cao; Yuan Ren (Toxicology, 2024)

Proliferacorins A–M: Thirteen undescribed acorane sesquiterpenoids isolated from the fungus Fusarium proliferatum - Alan Bao; Qin Li; Xiaotian Zhang; Meijia Zheng; Nanjin Ding; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Coordination environment engineering of MoS2-based nanocomposite by Ni atom incorporation for enhanced peroxymonosulfate activation - Minghao Fan; Conghui Wang; Xiang Yu; Jun Ding; Lei Yan; Gang Qin; Yue Li; Longlu Wang (Chemical Engineering Journal, 2024)

Comparison of soluble dietary fibers from various quinoa microgreens: Structural characteristics and bioactive properties - Ding-Tao Wu; Jie Li; Jin Wang; Jing Lei; Ren-You Gan; Peiyou Qin; Yi-Chen Hu; Xiao-Yong Wu; Liang Zou (Food Research International, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Impact of Bacillus subtilis and Pseudomonas fluorescens beneficial bacterial agents on soil-borne diseases, growth, and economics of continuous cropping of flue-cured tobacco - Huiqiong Ding; Chaosheng Luo; Yuanyuan Li; Qin Li; Yan Dong (Crop Protection, 2024)

Enhancing humoral and mucosal immune response of PED vaccine candidate by fusing S1 protein to nanoparticle multimerization - Minghui Li; Xueke Sun; Yilan Chen; Siqiao Wang; Qin Li; Yanan Wang; Yue Wang; Ruiqi Li; Peiyang Ding; Gaiping Zhang (Veterinary Microbiology, 2024)

Eighteen iridoids from the roots and rhizomes of Valeriana jatamansi and their protective effects against α-hemolysin - Yao Zhu; Peng-Ju Guo; Ao-Xue Ding; Liu Zheng; Gao-Xiang Du; Tong Chen; Guo-Qing Qin; Xiang-Gang Hu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

Monospecific and ultrasensitive detection of ofloxacin: A computational chemistry-assisted hapten screening strategy and analysis of molecular recognition mechanism - Jiaxu Xiao; Liangni Qin; Dan Zhao; Niexie Huang; Wennuo Xu; Linwei Zhang; Xiaoming Pan; Shiyun Han; Mingyue Ding; Long Li; Tao Le; Dapeng Peng (Journal of Hazardous Materials, 2024)

Unprecedented phytoplankton blooms in autumn/winter in the southern Bohai Sea (China) due to high Yellow River discharge: Implications of extreme rainfall events - Xiaokun Ding; Xiangyang Li; Aobo Wang; Xinyu Guo; Xiaotao Xu; Chenglei Liu; Xiaohan Qin; Yixuan Xie; Yuqiu Wei; Zhengguo Cui; Tao Jiang (Journal of Environmental Management, 2024)

Rapid in situ regeneration of phenol-saturated activated carbon fiber by an electro-permonosulfate-ozone process: Performance, operators and mechanism - Qin Xue; Biyu Yu; Mehary Dagnew; Wenli Li; Haojie Ding; Jian Zhang; Zhihua Sun; Pu Wang; Chun Zhao (Journal of Environmental Chemical Engineering, 2024)

Potential agricultural contamination and environmental risk of phthalate acid esters arrived from plastic film mulching - Jixiao Cui; Runhao Bai; Weili Ding; Qin Liu; Qi Liu; Wenqing He; Changrong Yan; Zhen Li (Journal of Environmental Chemical Engineering, 2024)

Functional graphitic carbon nitride/hydroxyapatite heterojunction for robust formaldehyde removal at ambient temperature - Zhihua Xu; Changle Li; Nenghuan Wang; Yingjie Ding; Zhaoxiong Yan; Qin Li (Journal of Environmental Chemical Engineering, 2024)

Selected pesticidal POPs and metabolites in the soil of five Vietnamese cities: Sources, fate, and health risk implications - Yang Ding; Shibin Qin; Huanfang Huang; Xiaoyan Tang; Xiushuang Li; Yuan Zhang; Wenwen Chen; Lan-Phuong Nguyen; Shihua Qi (Environmental Pollution, 2024)

A Multi-UAV Indoor Air Real-Time Detection and Gas Source Localization Method Based on Improved Teaching–Learning-Based Optimization - Jianqi Yang; Tao Ding; Qin Deng; Zesong Li; Yimin Wang; Jingjing Wu; Mingjuan Shi (Atmospheric Environment, 2024)

Performance analysis of microbial fuel cell - membrane bioreactor with reduced graphene oxide enhanced polypyrrole conductive ceramic membrane: Wastewater treatment, membrane fouling and microbial community under high salinity - Rui Wang; Hong You; Binghan Xie; Guoyu Zhang; Jing Zhu; Weirun Li; Xinan Dong; Qiqing Qin; Mengying Wang; Yi Ding; Haili Tan; Yuhong Jia; et al. (Science of The Total Environment, 2024)

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

Effects of konjac glucan-nan/low-acyl gellan edible coatings loaded thymol-β-cyclodextrin microcapsules on postharvest blueberry - Jie Ding; Chunyan Liu; Peng Huang; Hongying Li; Yan Liu; Dur E. Sameen; Yuwei Zhang; Yaowen Liu; Wen Qin (Food Chemistry, 2024)

Controllable growth of silver nanoparticles on titanium dioxide/nitrogen-doped carbon nanofiber/molybdenum disulfide: Toward enhanced photocatalytic-activating peroxymonosulfate performance and “memory catalysis” - Conghui Wang; Yue Li; Minghao Fan; Xiang Yu; Jun Ding; Lei Yan; Gang Qin; Jia Yang; Yongcai Zhang (Chemical Engineering Journal, 2024)

Rainfall erosivity index for monitoring global soil erosion - Lihong Wang; Yuechen Li; Yushi Gan; Long Zhao; Wei Qin; Lin Ding (CATENA, 2024)

Corrigendum: Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)

Digital finance, government intervention, and carbon emission efficiency in China - Keke Ding; Jing Li; Qin Wang (Environmental Science and Pollution Research, 2023)

Enzyme-sensitive soybean protein isolate/cinnamaldehyde antibacterial microcapsules triggered by blueberry proteases - Hui Li; Jie Ding; Jing Yan; Jianwu Dai; Suqing Li; Wen Qin; Yaowen Liu (Food Packaging and Shelf Life, 2023)

GRg1 inhibits the TLR4/NF-kB signaling pathway by upregulating miR-216a-5p to reduce growth factors and inflammatory cytokines in DR - Liping Xue; Min Hu; Qin Zhu; Yadi Li; Guanglong Zhou; Xiaofan Zhang; Yuan Zhou; Jieying Zhang; Peng Ding (Molecular Biology Reports, 2023)
Background Diabetic retinopathy (DR) is a common diabetic neurodegenerative disease that affects vision in severe cases. Current therapeutic drugs are ineffective for some patients with severe side effects, and ginsenoside-Rg1 (GRg1) has been shown to protect against DR and may serve as a new potential drug for DR. This study aimed to confirm the protective effect of GRg1 against DR and its molecular mechanism. Methods Human retinal microvascular endothelial cells (hRMECs) and rats were used to construct DR models in vitro and in vivo. Cell proliferation was detected by BrdU assays, the cell cycle was detected by flow cytometry, and TNF-α, IL-6 and IL-1β levels were detected by ELISA. qRT‒PCR, Western blotting and immunohistochemistry were used to detect the expression of related genes and proteins, and angiogenesis assays were used to assess angiogenesis. RIP and RNA pull down assays were used to determine the relationship between miR-216a-5p and TLR4; retinal structure and changes were observed by HE staining and retinal digestive spread assays. Results GRg1 effectively inhibited HG-induced hRMEC proliferation, cell cycle progression and angiogenesis and reduced the levels of intracellular inflammatory cytokines and growth factors. HG downregulated the expression of miR-216a-5p and upregulated the expression of TLR4/NF-kB signaling pathway-related proteins. Importantly, GRg1 inhibited TLR4/NF-kB signaling pathway activation by upregulating miR-216a-5p, thereby inhibiting HG-induced cell proliferation, cell cycle progression, angiogenesis, and the production of inflammatory cytokines and growth factors. In addition, animal experiments confirmed the results of the cell experiments. Conclusions GRg1 inhibits TLR4/NF-kB signaling by upregulating miR-216a-5p to reduce growth factors and inflammatory cytokines in DR, providing a potential therapeutic strategy for DR.

Long-term effect of acetate and biochar addition on enrichment and activity of denitrifying anaerobic methane oxidation microbes - Jing Ding; Fan Qin; Changxin Li; Mingfang Tang (Chemosphere, 2023)

Konjac glucomannan/low-acyl gellan gum edible coating containing thymol microcapsule regulates cell wall polysaccharides disassembly and delays postharvest softening of blueberries - Peng Huang; Jie Ding; Chunyan Liu; Hongying Li; Chenlin Wang; Yezi Lin; Dur E. Sameen; Md Alomgir Hossen; Mingrui Chen; Jing Yan; Yaowen Liu; Wen Qin (Postharvest Biology and Technology, 2023)

High-resolution luminescence chronology of loess-paleosols reveals East Asian summer monsoon and winter monsoon variation in Hexi Corridor during the past 25 kyr - Guoqiang Li; Yixuan Wang; Zhongfeng Yan; Caixin Qin; Weiping Ding; He Yang; Xiaoyan Wang; Xiaojian Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Advanced cobalt-ferrite layered double hydroxides sandwich-structured nanozymes for ROS-bloomed tumor therapy - Siyi Li; Xiucheng Zhao; He Ding; Jinhu Chang; Xiran Qin; Fei He; Xiangyang Gao; Shili Gai; Piaoping Yang (Chemical Engineering Journal, 2023)

Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)
The Beibu Gulf (Gulf of Tonkin, Vinh Bac Bo in Vietnamese), located midway along the East Asian-Australasian Flyway (EAAF), is a critical stopover and wintering region for migratory waterbirds. This transboundary coastal region, spanning between China and Vietnam, harbors diverse wetland habitats that provide refuge to waterbird species, including highly threatened species such as the spoon-billed sandpiper (CR) and the black-faced spoonbill (EN). However, the scarcity of comprehensive assessments regarding waterbird abundances, distribution, key wetland habitats, and regional threats hinders our understanding of its conservation significance at the flyway level. Further research is needed to address these knowledge gaps and facilitate effective conservation efforts in the Beibu Gulf. By synthesizing accessible citizen science datasets and published records from wetland sites in south China and northeast Vietnam, we concluded that at least 97 waterbird species used the Gulf’s wetlands during their annual cycle. Among surveys conducted from 2014 to 2022, 5 and 11 waterbird species were considered as first and second class protected species under the National Key Protected Wild Animal List in China; 2 species were listed as Critically Endangered on the IUCN Red List, 4 as Endangered and 2 as Vulnerable, underlying the critical importance of the Beibu Gulf for the survival of these species. Our study identified 25 sites in the Beibu Gulf that met the criteria for designation as internationally important wetlands. Alarmingly, less than a quarter (n = 5, or 20%) of these sites benefit from national or international protection. Localized threats, including aquatic resource harvesting, hunting, and aquaculture/fisheries, were widespread in the region. This study provides a crucial scientific baseline for continued waterbird monitoring, site prioritization, and the development of effective habitat management plans to conserve vital coastal wetland habitats in the Beibu Gulf in China and Vietnam.

Identification and contribution of potential sources to atmospheric lead pollution in a typical megacity: Insights from isotope analysis and the Bayesian mixing model - Wen-Jing Dai; Xiao-Dong Li; Yu-Cong Fu; Shi-Yuan Ding; Qin-Kai Li; Zhi-Qi Zhao (Science of The Total Environment, 2023)

OsGSTU5 and OsGSTU37 encoding glutathione reductases are required for cadmium tolerance in rice - Y. Yang; J. Li; H. Li; Y. Ding; W. Wu; R. Qin; J. Ni; R. Xu; P. Wei; J. Yang (International Journal of Environmental Science and Technology, 2023)

Suppression of Microglial ERO1a Alleviates Inflammation and Enhances the Efficacy of Rehabilitative Training After Ischemic Stroke - Jing Ren; Yuan Lv; Qiuyan Tian; Li Sun; Po Miao; Xiaofeng Yang; Li-Xiao Xu; Chen-Xi Feng; Mei Li; Qin Gu; Xing Feng; Xin Ding (Molecular Neurobiology, 2023)

Effectively facilitating the degradation of chloramphenicol by the synergism of Shewanella oneidensis MR-1 and the metal-organic framework - Xin Li; Shiling Zheng; Yinhao Li; Jiawang Ding; Wei Qin (Journal of Hazardous Materials, 2023)

Horseradish peroxidase (HRP) and glucose oxidase (GOX) based dual-enzyme system: Sustainable release of H2O2 and its effect on the desirable ping pong bibi degradation mechanism - Xiangyu Liu; Qian Zhang; Meng Li; Song Qin; Ziqi Zhao; Bing Lin; Yuwei Ding; Yutong Xiang; Chengwei Li (Environmental Research, 2023)

Facet-Controlled Cu-doped and K-promoted Fe2O3 nanosheets for efficient CO2 hydrogenation to liquid hydrocarbons - Chuan Qin; Yixiong Du; Ke Wu; Yanfei Xu; Rui Li; Haifeng Fan; Di Xu; Mingyue Ding (Chemical Engineering Journal, 2023)

Visualizing biogeochemical heterogeneity in soils and sediments: A review of advanced micro-scale sampling and imaging methods - Cai Li; Shiming Ding; Musong Chen; Zhilin Zhong; Qin Sun; Yan Wang (Critical Reviews in Environmental Science and Technology, 2023)

Efficient carbon removal and excellent anti-clogging performance have been achieved in multilayer quartz sand horizontal subsurface flow constructed wetland for domestic sewage treatment - Jieyue Li; Jiajun Wang; Qin Zhang; Yanli Ding; Yanan Zhang; Ronghua Wang; Dunqiu Wang; Shaoyuan Bai (Journal of Environmental Management, 2023)

N-Fluorobenzenesulfonimide as a multifunctional electrolyte additive for co-stabilizing dual-electrodes of lithium metal batteries with enhanced electrochemical performance - Xianjun Weng; Yanyang Qin; Xinyu Da; Yuanjun Zhao; Xuetian Deng; Bo Wen; Manying Cui; Xiangkai Yin; Yaqiong Su; Jiangxuan Song; Shujiang Ding; Xiaofei Hu; et al. (Chemical Engineering Journal, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

Adverse impacts of development on the deltamethrin-exposed host Ephestia elutella (Lepidoptera: Pyralidae) on population parameters of Habrobracon hebetor (Hymenoptera: Braconidae) - Xiu-Qin Wang; Hou-Ding Ou; Hao-Xi Li; Lan Wei; Yao Huang; Mao-Fa Yang (Crop Protection, 2023)

Sediment arsenic remediation by submerged macrophytes via root-released O2 and microbe-mediated arsenic biotransformation - Cai Li; Shiming Ding; Xin Ma; Yan Wang; Qin Sun; Zhilin Zhong; Musong Chen; Xianfang Fan (Journal of Hazardous Materials, 2023)

Airborne PM2.5 pollution: A double-edged sword modulating hepatic lipid metabolism in middle-aged male mice - Renjie Hu; Lu Zhang; Li Qin; Hao Ding; Ran Li; Weijia Gu; Rucheng Chen; Yunhui Zhang; Sanjay Rajagoplan; Kezhong Zhang; Qinghua Sun; Cuiqing Liu (Environmental Pollution, 2023)

Soil nitrogen transformation in different land use and implications for karst soil nitrogen loss controlling - Zhong-Jun Wang; Fu-Jun Yue; Li-Li Xue; Yu-Chun Wang; Cai-Qing Qin; Jie Zeng; Hu Ding; Yu-Cong Fu; Si-Liang Li (CATENA, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Influence of process water recirculation on hydrothermal carbonization of rice husk at different temperatures - Yan Ding; Debo Li; Maochao Lv; Longji Yuan; Jing Zhang; Shiru Qin; Baosu Wang; Xin Cui; Chuwen Guo; Peitao Zhao (Journal of Environmental Chemical Engineering, 2023)

Antibiotic resistance and resistance mechanism of Corynebacterium kroppenstedtii isolated from patients with mastadenitis - Qin Zhang; Shi Wu; Peipei Song; Yi Liu; Li Ding; Qingyu Shi; Xuan Zhu; Liyuan Zhang; Jun Zhang; Qin Wang; Jian Xu; Fupin Hu (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Pillar strategy enhanced ion transport and structural stability toward ultra-stable KVPO4F cathode for practical potassium-ion batteries - Jing Zhao; Yanyang Qin; Long Li; Hu Wu; Xin Jia; Xiaolong Zhu; Hongyang Zhao; Yaqiong Su; Shujiang Ding (Science Bulletin, 2023)

JARID2 regulates epithelial mesenchymal transition through the PTEN/AKT signalling pathways in ovarian endometriosis - Yiran Gu; Zhiyun Ding; Qin Zhou; Juan Li; Wenyan Qian (Reproductive Biology, 2023)

An iron-dependent form of non-canonical ferroptosis induced by labile iron - Yanmeng Li; Qin Ouyang; Wei Chen; Ke Liu; Bei Zhang; Jingyi Yao; Song Zhang; Junying Ding; Min Cong; Anjian Xu (Science China Life Sciences, 2023)

Air-Backed Aluminum Shells Subjected to Underwater Penetration: Torpedo Interception Simulations - Chucai Peng; Chufan Ding; Bin Chen; Xichen Sun; Weibing Li; Taotao Qin; Jun Feng (Journal of Marine Science and Engineering, 2023)
Underwater torpedoes have become a serious threat to ocean liners and warships, and the interception against attacking torpedoes is always the hotspot in marine engineering. To simulate the underwater torpedo interception by a high velocity projectile, this work numerically deals with the process of projectile water entry and sequent penetration into underwater aluminum shells, whereby conical and ogival nose projectiles are comparatively studied. With the arbitrary Lagrange–Euler (ALE) algorithm adopted to describe fluid medium, the projectile water entry model is developed and validated against the test data. Similarly, the penetration model validation is made by modeling a tungsten ball perforation on an aluminum plate. Covered by water fluid, the air-backed aluminum shell is utilized to simulate an underwater torpedo subjected to projectile impact. The numerical predictions of underwater penetration reveal that ogival nose projectiles have a superior performance in underwater motion and perforation while conical nose counterparts deteriorate the shell targets more severely. For 20 cm, 40 cm and 60 cm underwater depth scenarios, a numerical prediction suggests that the energy consumed by water is proportional to the water depth, meanwhile aluminum shell perforation absorbs almost the identical projectile kinetic energy. Such findings may shed some light on the nose shape optimization design of high velocity projectile intercepting underwater torpedoes.

Introducing water factors improves simulations of maize stomatal conductance models under plastic film mulching in arid and semi-arid irrigation areas - Cheng Li; Naijiang Wang; Xiaoqi Luo; Yue Li; Tibin Zhang; Dianyuan Ding; Qin'ge Dong; Hao Feng; Wenxin Zhang (Journal of Hydrology, 2023)

Effects of thymol concentration on postharvest diseases and quality of blueberry fruit - Jie Ding; Chunyan Liu; Peng Huang; Yuwei Zhang; Xinjie Hu; Hongying Li; Yan Liu; Liwei Chen; Yaowen Liu; Wen Qin (Food Chemistry, 2023)

Lotus leaf inspired sustainable and multifunctional Janus film for food packaging - Zhengxin Ma; Zeyuan Xing; Yao Zhao; Hongbo Zhang; Qiangwei Xin; Jie Liu; Meng Qin; Chunmei Ding; Jianshu Li (Chemical Engineering Journal, 2023)

Chemical constituents from the flowers of Cynanchum auriculatum Royle ex Wight - Xiaoxue Ding; Lu Wang; Yanling Xu; Shengnan Zheng; Shuang Wang; Lin Wang; Miao Qin; Shengbo Wu; Yi Yu; Jian Hong; Honglei Zhou; Lingchuan Xu; et al. (Biochemical Systematics and Ecology, 2023)

Highly Engrafting Cord Blood Hematopoietic Stem Cells are Enriched in CD34+ Cell Population with High Autophagy Activity - Qingwei Ding; Jingchao Zhou; Yu Li; Qin Wang; Chunxu Yao; Rongzhen Jiang; Qingyou Meng; Haitao Wang; Yandan Chen; Bin Guo (Stem Cell Reviews and Reports, 2023)

Effect of hydrodynamics on the transformation of nitrogen in river water by regulating the mass transfer performance of dissolved oxygen in biofilm - Mei Pan; Haizong Li; Xiangyun Han; Guixiang Quan; Weixing Ma; Qingyuan Guo; Xuan Li; Bairen Yang; Cheng Ding; Yuxi Chen; Tao Yun; Jiaojiao Qin; et al. (Chemosphere, 2023)

Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2023)

New record of explosive warmings in East Antarctica - Sai Wang; Minghu Ding; Ge Liu; Shoudong Zhao; Wenqian Zhang; Xichen Li; Wen Chen; Cunde Xiao; Dahe Qin (Science Bulletin, 2023)

Efficient removal of bisphenol A by a novel biochar-based Fe/C granule via persulfate activation: Performance, mechanism, and toxicity assessment - Xiang Li; Yang Qin; Huajing Song; Wei Zou; Zhiguo Cao; Linjie Ding; Yuwei Pan; Minghua Zhou (Process Safety and Environmental Protection, 2023)

Puerol and pueroside derivatives from Pueraria lobata and their anti-inflammatory activity - Ying-Jie Sun; Shi-Jie Cao; Feng-Ni Liang; Jin-Yan Li; Xiang-Yu Zhang; Wei Li; Li-Qin Ding; Feng Qiu (Phytochemistry, 2023)

Precision loading of Pd on Cu species for highly selective CO2 photoreduction to methanol - Xiaofang Shang; Guojun Li; Ruonan Wang; Tian Xie; Jie Ding; Qin Zhong (Chemical Engineering Journal, 2023)

Strict control of biomass burning inhibited particulate matter nitrate pollution over Tianjin: Perspective from dual isotopes of nitrate - Hao Xiao; Shi-Yuan Ding; Chuan-Wen Ji; Qin-Kai Li; Xiao-Dong Li (Atmospheric Environment, 2023)

Association between household air pollution and all-cause and cause-specific mortality: a systematic review and meta-analysis - Ning Li; Xianwei Guo; Yuyan Wu; Vicky Yau; Qiuxia Song; Wanying Su; Hao Wang; Qiwei Liang; Mingming Liang; Xiuxiu Ding; Scott Lowe; Yaru Li; et al. (Environmental Science and Pollution Research, 2023)

Altered Resting State Networks Before and After Temporal Lobe Epilepsy Surgery - Wei Li; Yuchao Jiang; Yingjie Qin; Xiuli Li; Du Lei; Heng Zhang; Ding Lei; Dezhong Yao; Cheng Luo; Qiyong Gong; Dong Zhou; Dongmei An (Brain Topography, 2022)

The effect of air pollution and emotional and behavioral problems on preschoolers’ overweight and obesity - Wanying Su; Qiuxia Song; Ning Li; Hao Wang; Xianwei Guo; Qiwei Liang; Mingming Liang; Xiuxiu Ding; Qirong Qin; Mingchun Chen; Liang Sun; Xiaoqin Zhou; et al. (Environmental Science and Pollution Research, 2022)

Characteristics and changes of the Himalayas glacial area in China during 1990–2015 - Shu-xian Shi; Li Xing; Yue-kai Ding; Jun Dong; Rui Liu; Qin Ji; Zuo-lin Xiao; Xun Huang (Journal of Mountain Science, 2022)

LncRNA OGFRP1 promotes cell proliferation and suppresses cell radiosensitivity in gastric cancer by targeting the miR-149-5p/MAP3K3 axis - Huihao Qin; Xing Li; Wei Zhang; Zhiqiang Ding (Journal of Molecular Histology, 2022)

East Asian summer monsoon changes in subtropical China since late Pleistocene: Evidence from the Ailuropoda-Stegodon fauna - Zhi-wen Li; Li Sun; Bao-sheng Li; Feng-nian Wang; Ding-ding Du; You-gui Song; Hui-Juan Zhang; Liu-qin Chen; Dan Xu (Journal of Mountain Science, 2022)

Predictability Limit of Monsoon Intraseasonal Precipitation: An Implication of Central Indian Ocean Mode - Jianhuang Qin; Lei Zhou; Ruiqiang Ding; Baosheng Li (Frontiers in Marine Science, 2022)
The prediction of monsoonal precipitation during Indian summer monsoon (ISM) remains difficult. Due to the high correlation between the Central Indian Ocean (CIO) mode index and the ISM precipitation variability, the predictability limit of the CIO mode index is investigated by the non-linear local Lyapunov exponent (NLLE) method in observations. Results show that the predictability limit of the CIO mode index can reach 38 days during boreal summer (from June to September), which is close to the upper predictability limit of intraseasonal precipitation (up to 40 days), and higher than the predictability limits of dynamical monsoon indices (under 3 weeks) and boreal summer intraseasonal oscillation (BSISO) indices (around 30 days). Such high predictability limit of the CIO mode index is mainly attributable to the long predictability limits from the intraseasonal sea surface temperature (SST) and intraseasonal zonal wind, which are the components of the CIO mode. As a result, the CIO mode is expected to extend the predictability of monsoonal precipitation, and benefits to improve the prediction skills of the ISM.

Two new isoquinoline alkaloids from the seeds of Nandina domestica - Juan Qin; Sheng-Yuan Zhang; Yu-Bo Zhang; Li-Feng Chen; Neng-Hua Chen; Zhong-Nan Wu; Ding Luo; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2021)

Lithological and environmental controls on large tafoni along conglomerate cliffs in subtropic humid Danxiashan UNESCO Global Geopark - Xin Chen; Liu-qin Chen; Yan-hong Zhang; Ding-ding Du; Hai-ping Hu; Dong-xing Liu; Wen-zhuo Li (Journal of Mountain Science, 2021)

Exploring and quantifying the relationship between instantaneous wind speed and turbidity in a large shallow lake: case study of Lake Taihu in China - Wenhao Ding; Jinxiao Zhao; Boqiang Qin; Tingfeng Wu; Senlin Zhu; Yun Li; Shikai Xu; Shiping Ruan; Yong Wang (Environmental Science and Pollution Research, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Influence of plant coverage and environmental variables on pollen productivities: evidence from northern China - Kaixiu Zhang; Wen Qin; Fang Tian; Xianyong Cao; Yuecong Li; Jule Xiao; Wei Ding; Ulrike Herzschuh; Qinghai Xu (Frontiers of Earth Science, 2020)

New potential strains for controlling Spodoptera frugiperda in China: Cordyceps cateniannulata and Metarhizium rileyi - Ye-Ming Zhou; Wen Xie; Jia-Qin Ye; Tao Zhang; Ding-Yin Li; Jun-Rui Zhi; Xiao Zou (BioControl, 2020)

Slope failure of biotreated sand embankments under rainfall conditions: experimental investigation and numerical simulation - Zhaoyu Wang; Qi Li; Nan Zhang; Yong Jin; Haibo Qin; Jinhua Ding (Bulletin of Engineering Geology and the Environment, 2020)

Effects of an oasis protective system on aeolian sediment deposition: a case study from Gelintan oasis, southeastern edge of the Tengger Desert, China - Jing Ding; Yun-hu Xie; Xiao-jia Li; Hong-tao Jiang; Ji Wang; Xiao-xi Liu; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai (Journal of Mountain Science, 2020)

Duration of SARS-CoV-2 viral shedding during COVID-19 infection - Guo-Qing Qian; Xue-Qin Chen; Ding-Feng Lv; Ada Hoi Yan Ma; Li-Ping Wang; Nai-Bin Yang; Xiao-Min Chen (Infectious Diseases, 2020)

Plant abiotic stress response and nutrient use efficiency - Zhizhong Gong; Liming Xiong; Huazhong Shi; Shuhua Yang; Luis R. Herrera-Estrella; Guohua Xu; Dai-Yin Chao; Jingrui Li; Peng-Yun Wang; Feng Qin; Jijang Li; Yanglin Ding; et al. (Science China Life Sciences, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Antagonistic regulation of axillary bud outgrowth by the BRANCHED genes in tobacco - Na Ding; Qiulin Qin; Xia Wu; Robert Miller; David Zaitlin; Dandan Li; Shengming Yang (Plant Molecular Biology, 2020)

Synthesis and plant growth regulatory activities of 2′,3′-PhABA and iso-2′,3′-PhABA esters - Chuan Wan; Jiaqi Li; Fenghai Zhao; Dongyan Yang; Chuanliang Che; Shanshan Ding; Yimin Hu; Yumei Xiao; Zhaohai Qin (Molecular Diversity, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Effects of dietary protein level on growth performance, digestive enzyme activity, and gene expressions of the TOR signaling pathway in fingerling Pelteobagrus fulvidraco - Qin Qin; Xiu-Fei Cao; Yong-jun Dai; Li-Na Wang; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2019)

Snowmelt modeling using two melt-rate models in the Urumqi River watershed, Xinjiang Uyghur Autonomous Region, China - Muattar Saydi; Jian-li Ding; Vasit Sagan; Yan Qin (Journal of Mountain Science, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Two pairs of phenolic enantiomers from the leaves of Eucommia ulmoides Oliver - Jian-Kun Yan; Xu-Liu Shi; Paul Owusu Donkor; Xiu-Mei Gao; Li-Qin Ding; Feng Qiu (Natural Product Research, 2019)

KIAA1199 promotes invasion and migration in non-small-cell lung cancer (NSCLC) via PI3K-Akt mediated EMT - Zhiyuan Tang; Yang Ding; Qin Shen; Caixin Zhang; Jun Li; Mohammed Nazar; Yan Wang; Xiaoyu Zhou; Jianfei Huang (Journal of Molecular Medicine, 2019)

A 55 K SNP array-based genetic map and its utilization in QTL mapping for productive tiller number in common wheat - Jiajun Liu; Wei Luo; Nana Qin; Puyang Ding; Han Zhang; Congcong Yang; Yang Mu; Huaping Tang; Yaxi Liu; Wei Li; Qiantao Jiang; Guoyue Chen; et al. (Theoretical and Applied Genetics, 2018)

Three new 3,4-seco-cycloartane triterpenes from Gardenia sootepensis - Wei-Wu Song; Xue-Qin Wang; Hua-Li Jia; Zheng-Kun Zhang; Yong-Jie Ding; Ya-Hong Chen (Natural Product Research, 2018)

The phosphatidylinositol synthase gene (GhPIS) contributes to longer, stronger, and finer fibers in cotton - Qin Long; Fang Yue; Ruochen Liu; Shuiqing Song; Xianbi Li; Bo Ding; Xingying Yan; Yan Pei (Molecular Genetics and Genomics, 2018)

High-Temperature Metamorphism, Anataxis and Tectonic Evolution of a Mafic Granulite from the Eastern Himalayan Orogen - Zeming Zhang; Huixia Ding; Xin Dong; Zuolin Tian; Dongyan Kang; Hongchen Mu; Shengkai Qin; Yuanyuan Jiang; Mengmei Li (Journal of Earth Science, 2018)

The key gluconeogenic gene PCK1 is crucial for virulence of Botrytis cinerea via initiating its conidial germination and host penetration - Jian‐Kang Liu; Hao‐Wu Chang; Yue Liu; Yu (Haity) Qin; Yu‐Han Ding; Lan Wang; Yue Zhao; Ming‐Zhe Zhang; Sheng‐Nan Cao; Le‐Tao Li; Wei Liu; Gui‐Hua Li; et al. (Environmental Microbiology, 2018)
Summary The process of initiation of host invasion and survival of some foliar phytopathogenic fungi in the absence of external nutrients on host leaf surfaces remains obscure. Here, we demonstrate that gluconeogenesis plays an important role in the process and nutrient‐starvation adaptation before the pathogen host invasion. Deletion of phosphoenolpyruvate c arboxy k inase gene BcPCK1 in gluconeogenesis in Botrytis cinerea , the causative agent of grey mould, resulted in the failure of the Δ Bcpck1 mutant conidia to germinate on hard and hydrophobic surface and penetrate host cells in the absence of glucose, reduction in conidiation and slow conidium germination in a nutrient‐rich medium. The wild‐type and Δ Bcpck1 conidia germinate similarly in the presence of glucose (higher concentration) as the sole carbon source. Conidial glucose‐content should reach a threshold level to initiate germination and host penetration. Infection structure formation by the mutants displayed a glucose‐dependent fashion, which corresponded to the mutant virulence reduction. Exogenous glucose or complementation of BcPCK1 completely rescued all the developmental and virulence defects of the mutants. Our findings demonstrate that BcPCK1 plays a crucial role in B. cinerea pathogenic growth and virulence, and provide new insights into gluconeogenesis mediating pathogenesis of plant fungal pathogens via initiation of conidial germination and host penetration.

Identification of QTLs associated with heat tolerance at the heading and flowering stage in rice (Oryza sativa L.) - Mao-mao Li; Xia Li; Li-qin Yu; Jin-wen Wu; Hui Li; Jin Liu; Xiao-ding Ma; Su-min Jo; Dong-Soo Park; Youchun Song; Dongjin Shin; Long-zhi Han (Euphytica, 2018)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)

Assessing the efficacy of three methionine sources in low protein and low fish meal diet for Chinese soft-shelled turtle, Pelodiscus sinensis - Fan Zhou; Ya-Qin Wang; Yi-Jiang Bei; Wing-Keong Ng; Ding-Nan Wang; Shi-Yan Li; Qing-Hui Meng; Xue-Yan Ding (Aquaculture International, 2018)

Microsatellite records for volume 9, issue 4 - Zhaosheng Cai; Wenxuan Cao; Jie Chen; Jiayin Dai; Ge Ding; Samantha Gray; Jiasheng Hao; Xiayun Jiang; B. B. Li; Yao Li; Z. B. Li; Gang Liu; et al. (Conservation Genetics Resources, 2017)

Neuroprotection and CD131/GDNF/AKT Pathway of Carbamylated Erythropoietin in Hypoxic Neurons - Jing Ding; Jing Wang; Qin-Ying Li; Jie-Zhong Yu; Cun-Gen Ma; Xin Wang; Chuan-Zhen Lu; Bao-Guo Xiao (Molecular Neurobiology, 2017)

Long-term dynamic characterization of aeolian desertification in northwest Shanxi, China - Zhanjin Xue; Zuodong Qin; Fangqin Cheng; Guangwei Ding; Hongjian Li (Environmental Science and Pollution Research, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Snowdrift effect on snow deposition: Insights from a comparison of a snow pit profile and meteorological observations in east Antarctica - MingHu Ding; Tong Zhang; CunDe Xiao; ChuanJin Li; Bo Jin; LinGen Bian; ShuJie Wang; DongQi Zhang; DaHe Qin (Science China Earth Sciences, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

Enterovirga rhinocerotis gen. nov., sp. nov., isolated from Rhinoceros unicornis faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Hui Lei; Yi Jiang; Li Han; Xue-Shi Huang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2017)

Relationships between the extratropical ENSO precursor and leading modes of atmospheric variability in the Southern Hemisphere - Jianhuang Qin; Ruiqiang Ding; Zhiwei Wu; Jianping Li; Sen Zhao (Advances in Atmospheric Sciences, 2017)

Anti-phytopathogen, multi-target acetylcholinesterase inhibitory and antioxidant activities of metabolites from endophytic Chaetomium globosum - Wei Li; Xueqiong Yang; Yabin Yang; Rongting Duang; Guangyi Chen; Xiaozhan Li; Qiling Li; Shaohuan Qin; Shuquan Li; Lixing Zhao; Zhongtao Ding (Natural Product Research, 2016)

Patterns and drivers of soil microbial communities in Tibetan alpine and global terrestrial ecosystems - Yong‐Liang Chen; Jin‐Zhi Ding; Yun‐Feng Peng; Fei Li; Gui‐Biao Yang; Li Liu; Shu‐Qi Qin; Kai Fang; Yuan‐He Yang (Journal of Biogeography, 2016)
Aim Soil microorganisms play key roles in regulating many important ecosystem processes. However, our understanding of the patterns and drivers of soil microbial communities remains limited. This study aims to test the hypothesis that edaphic factors are more important in explaining variations in soil microbial communities than climatic and biotic factors, as soils directly provide substrates and environment for soil microbial communities. Location Tibetan alpine grasslands and global terrestrial biomes. Methods On the basis of phospholipid fatty acid ( PLFA ) analysis, we investigated large‐scale patterns and drivers of soil microbial communities using data obtained from 196 sites within two major grassland types (alpine steppe and alpine meadow) on the Tibetan Plateau. We also explored global patterns of soil microbial communities by analysing published data from around the world. Results Soil microbial PLFA s in Tibetan alpine grasslands were positively associated with mean annual temperature and mean annual precipitation ( MAP ), contradicting patterns previously observed across global biomes. A combined stepwise regression and variation partitioning analysis revealed that soil microbial community variations in Tibetan alpine grasslands were mainly explained by edaphic factors, such as soil organic carbon, C : N ratio, pH and soil texture, then by biotic factors, such as aboveground biomass and plant species richness, and further by climatic factors, such as MAP . The global analysis confirmed that edaphic factors accounted for a greater portion of the variation in soil microbial communities than did climatic and biotic variables. Main conclusions These results provide strong support for the hypothesis that edaphic factors are the dominant drivers of spatial variations in soil microbial communities across regional and global scales.

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Genetic Diversity Analysis of Sugarcane Germplasm Based on Fluorescence-Labeled Simple Sequence Repeat Markers and a Capillary Electrophoresis-based Genotyping Platform - Qian You; Yong-Bao Pan; Li-Ping Xu; Shi-Wu Gao; Qin-Nan Wang; Ya-Chun Su; Yong-Qing Yang; Qi-Bin Wu; Ding-Gang Zhou; You-Xiong Que (Sugar Tech, 2016)

The permafrost carbon inventory on the Tibetan Plateau: a new evaluation using deep sediment cores - Jinzhi Ding; Fei Li; Guibiao Yang; Leiyi Chen; Beibei Zhang; Li Liu; Kai Fang; Shuqi Qin; Yongliang Chen; Yunfeng Peng; Chengjun Ji; Honglin He; et al. (Global Change Biology, 2016)
The permafrost organic carbon ( OC ) stock is of global significance because of its large pool size and the potential positive feedback to climate warming. However, due to the lack of systematic field observations and appropriate upscaling methodologies, substantial uncertainties exist in the permafrost OC budget, which limits our understanding of the fate of frozen carbon in a warming world. In particular, the lack of comprehensive estimates of OC stocks across alpine permafrost means that current knowledge on this issue remains incomplete. Here, we evaluated the pool size and spatial variations of permafrost OC stock to 3 m depth on the Tibetan Plateau by combining systematic measurements from a substantial number of pedons ( i.e . 342 three‐metre‐deep cores and 177 50‐cm‐deep pits) with a machine learning technique ( i.e . support vector machine, SVM ). We also quantified uncertainties in permafrost carbon budget by conducting Monte Carlo simulations. Our results revealed that the combination of systematic measurements with the SVM model allowed spatially explicit estimates to be made. The OC density ( OC amount per unit area, OCD ) exhibited a decreasing trend from the south‐eastern to the north‐western plateau, with the exception that OCD in the swamp meadow was substantially higher than that in surrounding regions. Our results also demonstrated that Tibetan permafrost stored a large amount of OC in the top 3 m, with the median OC pool size being 15.31 Pg C (interquartile range: 13.03–17.77 Pg C). 44% of OC occurred in deep layers ( i.e . 100–300 cm), close to the proportion observed across the northern circumpolar permafrost region. The large carbon pool size together with significant permafrost thawing suggests a risk of carbon emissions and positive climate feedback across the Tibetan alpine permafrost region.

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

Advanced oxidative protein products induced human keratinocyte apoptosis through the NOX–MAPK pathway - Baihui Sun; Ruoting Ding; Wenlin Yu; Yanhong Wu; Bulin Wang; Qin Li (Apoptosis, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Proteome analysis of pollen in the K-type male sterility line 732A and its maintainer 732B in wheat (Triticum aestivum L.) by two-dimensional gel electrophoresis - Fangning Zhang; Guidong Li; Qin Ding; Zhen Wang; Xiaofei Ma; Hongxia Zhang; Zigang Zhang; Feng Jin; Lingjian Ma (Acta Physiologiae Plantarum, 2016)

Silicon Application Alleviates Drought Stress in Wheat Through Transcriptional Regulation of Multiple Antioxidant Defense Pathways - Dongyun Ma; Dexiang Sun; Chenyang Wang; Haixia Qin; Huina Ding; Yaoguang Li; Tiancai Guo (Journal of Plant Growth Regulation, 2016)

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

A new polyoxygenated farnesylcyclohexenone from Fungus Penicillium sp. - Yabin Yang; Fangfang Yang; Lixing Zhao; Rongting Duang; Guangyi Chen; Xiaozhan Li; Qiling Li; Shaohuan Qin; Zhongtao Ding (Natural Product Research, 2016)

An artificially constructed Syngonium podophyllum-Aspergillus niger combinate system for removal of uranium from wastewater - Jia-dong He; Yong-dong Wang; Nan Hu; Dexin Ding; Jing Sun; Qin-wen Deng; Chang-wu Li; Fei Xu (Environmental Science and Pollution Research, 2015)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

A 2680-year record of sea ice extent in the Ross Sea and the associated atmospheric circulation derived from the DT401 East Antarctic ice core - ChuanJin Li; JiaWen Ren; CunDe Xiao; ShuGui Hou; MingHu Ding; DaHe Qin (Science China Earth Sciences, 2015)

Biological Modulation of Mouse RPE Cells in Response to Subthreshold Diode Micropulse Laser Treatment - Zhouyue Li; Yanping Song; Xiao Chen; Zhongshan Chen; Qin Ding (Cell Biochemistry and Biophysics, 2015)

Sphingobacterium rhinocerotis sp. nov., isolated from the faeces of Rhinoceros unicornis - Gui-Ding Li; Xiu Chen; Qin-Yuan Li; Fang-Ji Xu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2015)

Surface mass balance and its climate significance from the coast to Dome A, East Antarctica - MingHu Ding; CunDe Xiao; ChuanJin Li; DaHe Qin; Bo Jin; GuiTao Shi; AiHong Xie; XiangBin Cui (Science China Earth Sciences, 2015)

A new natural nucleotide and other antibacterial metabolites from an endophytic Nocardia sp. - Wei Li; Xueqiong Yang; Yabin Yang; Shaohuan Qin; Qiling Li; Lixing Zhao; Zhongtao Ding (Natural Product Research, 2015)

Spatial distribution of marine chemicals along a transect from Zhongshan Station to the Grove Mountain area, Eastern Antarctica - Xiang Qin; ChuanJin Li; CunDe Xiao; ShuGui Hou; MingHu Ding; JiaWen Ren; DaHe Qin (Science China Earth Sciences, 2014)

Sunitinib mesylate inhibits proliferation of human colonic stromal fibroblasts in vitro and in vivo - Zhan-huai Wang; Qiong Li; Shu-qin Ruan; Qian Xiao; Yue Liu; Ye-ting Hu; Li-feng Hu; Hai-yan Chen; Shu Zheng; Su-zhan Zhang; Ke-feng Ding (Journal of Zhejiang University-SCIENCE B, 2014)

Novel antimicrobial metabolites produced by Sika deer-associated Actinomyces sp. JN411010 - Yujiao Tang; Yanmei Wang; Zhaohui Wang; Jing Zhang; Jianchun Qin; Quankai Wang; Lihua Yang; Lingzhi Xu; Yuling Ding; Yang Guo; Hongliang Li; Jingsi Li; et al. (Natural Product Research, 2013)

Factors controlling the nitrate in the DT-401 ice core in eastern Antarctica - ChuanJin Li; JiaWen Ren; DaHe Qin; CunDe Xiao; ShuGui Hou; YuanSheng Li; MingHu Ding (Science China Earth Sciences, 2013)

Temporal and spatial variations of global solar radiation over the Qinghai–Tibetan Plateau during the past 40 years - Ren Li; Lin Zhao; Tonghua Wu; Yongjian Ding; Yufei Xin; Defu Zou; Yao Xiao; Yongliang Jiao; Yanhui Qin; Linchan Sun (Theoretical and Applied Climatology, 2013)

Disruption of the transcription factor RBP-J results in osteopenia attributable to attenuated osteoclast differentiation - Jing Ma; Ya-Li Liu; Yi-Yang Hu; Ya-Ning Wei; Xing-Cheng Zhao; Guang-Ying Dong; Hong-Yan Qin; Yin Ding; Hua Han (Molecular Biology Reports, 2013)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

The monitoring results of electromagnetic radiation of 110-kV high-voltage lines in one urban location in Chongqing P.R. China - Qi-zhong Qin; Yu Chen; Ting-ting Fu; Li Ding; Ling-li Han; Jian-chao Li (Environmental Monitoring and Assessment, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

Screening of Plant Species for Phytoremediation of Uranium, Thorium, Barium, Nickel, Strontium and Lead Contaminated Soils from a Uranium Mill Tailings Repository in South China - Guang-yue Li; Nan Hu; De-xin Ding; Ji-fang Zheng; Yu-long Liu; Yong-dong Wang; Xiao-qin Nie (Bulletin of Environmental Contamination and Toxicology, 2011)

Analysis of bacterial communities in rhizosphere soil of healthy and diseased cotton (Gossypium sp.) at different plant growth stages - Yan Zhang; Bing-Hai Du; Zhi-gang Jin; Zheng-hua Li; Hong-ning Song; Yan-Qin Ding (Plant and Soil, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

Regulation of Cell Division and Growth in Roots of Lactuca sativa L. Seedlings by the Ent-Kaurene Diterpenoid Rabdosin B - Lan Ding; Hongwei Jing; Bo Qin; Linlin Qi; Jing Li; Tao Wang; Guoan Liu (Journal of Chemical Ecology, 2010)

Separation and elucidation of anthocyanins in the fruit of mockstrawberry ( Duchesnea indica Focke) - Chuanguang Qin; Yang Li; Ruijie Zhang; Weining Niu; Yan Ding (Natural Product Research, 2009)

Effects of upregulated expression of microRNA-16 on biological properties of culture-activated hepatic stellate cells - Can-Jie Guo; Qin Pan; Bo Jiang; Guang-Yu Chen; Ding-Guo Li (Apoptosis, 2009)

Isolation, Antimicrobial Activity, and Metabolites of Fungus Cladosporium sp. Associated with Red Alga Porphyra yezoensis - Ling Ding; Song Qin; Fuchao Li; Xiaoyuan Chi; Hartmut Laatsch (Current Microbiology, 2008)

Retention capacities of several bryophytes for Hg(II) with special reference to the elevation and morphology of moss growth - Shou-Qin Sun; Ding-Yong Wang; Ming He; Xian-Yuan Li; Cheng Zhang (Environmental Monitoring and Assessment, 2007)